Ras signaling and RREB1 are required for the dissociation of medial edge epithelial cells in murine palatogenesis - Toshihiro Inubushi; Ayaka Fujiwara; Takumi Hirose; Gozo Aoyama; Toshihiro Uchihashi; Naoki Yoshida; Yuki Shiraishi; Yu Usami; Hiroshi Kurosaka; Satoru Toyosawa; Susumu Tanaka; Tetsuro Watabe; et al. (The Company of Biologists, 2022)
Cleft palate is one of the major congenital craniofacial birth defects. The etiology underlying the pathogenesis of cleft palate has yet to be fully elucidated. Dissociation of the medial edge epithelium (MEE) at the contacting region of palatal shelves and subsequent migration or apoptosis of MEE cells is required for proper MEE removal. Ras-responsive element-binding protein 1 (RREB1), a RAS transcriptional effector, has recently been shown to play a crucial role in developmental epithelial-mesenchymal transition (EMT), in which loss of epithelial characteristics is an initial step, during mid-gastrulation of embryonic development. Interestingly, the involvement of RREB1 in cleft palate has been indicated in humans. Here, we demonstrated that pan-Ras inhibitor prevents the dissociation of MEE during murine palatal fusion. Rreb1 is expressed in the palatal epithelium during palatal fusion, and knockdown of Rreb1 in palatal organ culture resulted in palatal fusion defects by inhibiting the dissociation of MEE cells. Our present findings provide evidence that RREB1-mediated Ras signaling is required during palatal fusion. Aberrant RREB1-mediated Ras signaling might be involved in the pathogenesis of cleft palate.